1999
DOI: 10.1002/hep.510290119
|View full text |Cite
|
Sign up to set email alerts
|

Transient Selection of A Hepatitis B Virus Polymerase Gene Mutant Associated With A Decreased Replication Capacity and Famciclovir Resistance

Abstract: Prolonged therapy for chronic hepatitis B (HBV) with nucleoside analogs may result in the emergence of HBV mutants resistant to antivirals. Here, we describe the transient selection of an HBV polymerase gene mutant that was associated with viral persistence in an immune competent patient treated with famciclovir. Viral polymerase gene sequence was analyzed directly on polymerase chain reaction (PCR) products and also after cloning. The results showed the transient selection of a V542I mutant in the C domain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
70
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 40 publications
2
70
0
2
Order By: Relevance
“…18,20 However, several recent reports have indicated that penciclovir has high IC 50 values in the range of 82 µmol/L to 100 µmol/L. 38,47,48 The lower potency of penciclovir, compared with adefovir and lamivudine, for the inhibition of HBV polymerase and HBV replication in vitro is more consistent with the apparent lower efficacy of famciclovir compared with adefovir and lamivudine in recently published clinical studies. Patients treated with 30 mg adefovir daily for 12 weeks displayed Ն99.99% decreases in median serum HBV-DNA levels from baseline.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…18,20 However, several recent reports have indicated that penciclovir has high IC 50 values in the range of 82 µmol/L to 100 µmol/L. 38,47,48 The lower potency of penciclovir, compared with adefovir and lamivudine, for the inhibition of HBV polymerase and HBV replication in vitro is more consistent with the apparent lower efficacy of famciclovir compared with adefovir and lamivudine in recently published clinical studies. Patients treated with 30 mg adefovir daily for 12 weeks displayed Ն99.99% decreases in median serum HBV-DNA levels from baseline.…”
Section: Discussionmentioning
confidence: 78%
“…Our in vitro enzymatic assays indicated that the V555I mutation in HBV polymerase was clearly associated with a phenotypic resistance to famciclovir. This mutation has also recently been shown to be resistant to penciclovir in a cell culture model of HBV replication by Pichoud et al 38 The valine to isoleucine mutation at position 555 may directly interfere with the binding of PCVTP to HBV polymerase or indirectly interfere by inducing a conformational change in the PCVTP binding site. The exact mode of PCVTP binding to HBV polymerase is unknown because of the lack of a crystal structure for the complex HBV polymerase.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations